Nutrition Goes to School: Promoting Nutrition and Healthy Eating Awareness in School Community - Muslihah, Nurul; Maulidiana, Annisa Rizky; Habibie, Intan Yusuf; Nastaina, Hayu Iyaka (Department of Nursing, Faculty of Health Sciences, Universitas Brawijaya., 2026)
Children's health and cognitive development are fundamental determinants of future human capital. In Indonesia, nutritional problems such as stunting, anemia, and obesity remain prevalent, including among school-aged children. Suboptimal nutritional status may hinder physical growth, cognitive development, and academic performance. In response to these challenges, the Nutrition Goes to School: Healthy and Smart Children program was implemented to improve parents' knowledge and awareness of the importance of healthy eating and balanced nutrition in supporting children's growth and development. The program was conducted at RA Al-Jauhar, Ngijo, Karangploso, Malang Regency, targeting parents of enrolled students. The implementation consisted of internal team coordination, coordination with the school, and interactive nutrition education sessions. Educational materials were delivered through a combination of lectures, group discussions, games, and practical simulations to facilitate participants' understanding and encourage the application of healthy eating practices at home. Program effectiveness was evaluated using pre-test and post-test assessments to measure changes in participants' knowledge. The results demonstrated a significant improvement (p=0.003) in the mean knowledge score, increasing from 63.2±20.1 before the intervention to 73.2±21.6 after the intervention. This improvement indicates the program's effectiveness in enhancing participants' understanding of balanced nutrition and its practical application in daily life. Participants also actively engaged in discussions, asked questions, and shared their experiences throughout the sessions. Follow-up mentoring after the training further supported the implementation of the educational messages at home, promoting consistent healthy eating behaviors among children. Overall, the program proved to be effective and responsive to the needs of the target population. Similar initiatives could be expanded to higher educational levels to strengthen nutrition awareness and healthy dietary behaviors across different age groups.